A SYNOPSIS OF THE EARLY DEVELOPMENTAL STAGES OF FISHES OF THE GENUS SARDINELLA VALENCIENNES FROM INDIAN WATERS WITH KEYS FOR THEIR IDENTIFICATION - Bensam, P (Indian Journal of Fisheries, 2011)
In the present synopsis, a brief resume of relevant literature published on the early stages of Sardinella species is given, along with keys prepared for identification of the eggs, larvae and posflarvae, to the extent available. Some of the subtle characters to distinguish the eggs, larvae and postlarave of the species described are brought out for their easy separation in plankton studies.